A Configural Theory of Team Processes: Accounting for the Structure of Taskwork and Teamwork - Crawford, Eean R.; LePine, Jeffery A. (Academy of Management Review, 2013)
Theories of team processes have focused on content and temporal relevance, while largely ignoring implications of structure. We apply social network concepts to propose theory that articulates structural configurations of taskwork and teamwork processes in terms of closure, centralization, and subgrouping. Our theory challenges the conventional view that increases in team processes are inherently and uniformly beneficial and explains how structural configurations involve trade-offs that must be acknowledged in our research and practice.